Heterostructure composite catalyst as well as preparation method and application thereof
By dispersing trimanganese tetraoxide particles and Lewis acid compound particles on the surface of the nickel-iron layered double hydroxide catalyst, the problem of insufficient activity and stability of nickel-iron layered double hydroxide in low-concentration alkali solution is solved, and the problem of insufficient activity and stability of nickel-iron layered double hydroxide in low-concentration alkali solution is achieved. Efficient water decomposition and hydroforming reaction to produce hydrogen and electrolyzing water.
Patent Information
- Application Number
- CN202411452381.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-24
AI Technical Summary
In the prior art, nickel-iron layered double hydroxide (NiFe-LDH) is a basic OER catalyst with low activity and poor stability under industrial-grade current density in low concentration alkali solution.
Using heterostructure composite catalyst, including the formation of nickel-iron layered double hydroxide on the substrate, and spreading trimanganese tetraoxide particles on its surface, the OH-ion concentration on the catalyst surface during electrolysis is increased through the Lewis acid compound particles, and the protons are reduced Damage to the catalyst and improve stability.
Improve the activity and stability of the catalyst in low-concentration alkali liquid, avoid the problems of anionic ionomer bonding and chemical stability, and enhance the operating stability of the anion exchange membrane electrolyte cell.
Smart Images

Figure CN119177469A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a heterogeneous structure composite catalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen, as a new energy source with a wide range of sources, flexibility, efficiency, cleanness and renewable, plays an important role in accelerating the process of green and low-carbon development. As the most direct means of obtaining hydrogen, water electrolysis is considered to be the most promising low-carbon technology. While producing high calorific value hydrogen, it can also be coupled with sustainable clean energy such as solar energy and wind energy, and is one of the important options for achieving large-scale green hydrogen production.
[0003] The electrolytic water splitting reaction can generally be divided into the oxygen evolution reaction (OER) at the anode and the hydrogen evolution reaction (HER) at the cathode. Compared with HER, OER involves a multi-proton coupled electron transfer step, and the reaction kinetics are slower. OER is also considered to be the bottleneck step of the entire water splitting process. Therefore, the development of efficient and stable OER catalysts is of vital research significance for achieving efficient water splitting and hydrogen production.
[0004] As a new type of water electrolysis technology, anion exchange membrane electrolyzer (AEM-WE) not only has the low cost characteristics of traditional alkaline electrolyzer (AWE) technology, but also effectively inherits the advantages of proton exchange membrane electrolyzer (PEM-WE) such as compact packaging, fast response time, large pressure difference and high operating current density (≧2.0A cm -2 ) advantage, and is the first choice for large-scale production of green hydrogen in the future. At present, in the anion exchange membrane water electrolysis technology, when high concentration alkaline solution (≧1.0M) is used as the electrolyte, AEM-WE has an industrial current density (≧0.5A cm -2 ) can run stably for thousands of hours under high temperature, showing a wide range of industrial application scenarios. However, the use of high-concentration alkali solution will not only corrode the electrolysis equipment and increase maintenance costs, but also cause safety hazards. In order to comply with the concept of green development, the use of pure water instead of high-concentration alkali solution is the most ideal choice. But the low OH content of pure water solution - The ion concentration requires the use of anionic ionomers as OH in the membrane electrode assembly process. - The weak bonding force and chemical stability of anionic ionomers will seriously affect the stability of AEM-WE and reduce its energy conversion efficiency. The use of low-concentration alkali solution can effectively avoid the use of anionic ionomers. - ions, it can also alleviate corrosion and safety issues.
[0005] Nickel-iron layered double hydroxide (NiFe-LDH) has been widely reported as one of the alkaline OER catalysts with excellent performance. However, the alkaline OER catalyst based on nickel-iron layered double hydroxide (NiFe-LDH) in the prior art has poor performance under industrial-grade current density working conditions in low-concentration alkaline solution (low-concentration alkaline solution refers to the alkaline solution with an alkali concentration of less than or equal to 1.0 mol / L) (industrial-grade current density refers to current density ≥ 0.5 Acm -2 ) have low activity and poor stability. Summary of the invention
[0006] Therefore, the technical problem to be solved by the present invention is to overcome the defects of nickel-iron layered double hydroxide (NiFe-LDH) in the prior art as an alkaline oxygen evolution reaction catalyst having low activity and poor stability under working conditions at industrial-grade current density in a low-concentration alkaline solution, thereby providing a heterogeneous structure composite catalyst and its preparation method and use.
[0007] The invention provides a heterogeneous structure composite catalyst, comprising: a substrate, nickel-iron layered double hydroxide located on the surface of the substrate, and manganese manganese tetroxide particles dispersed on the surface of the nickel-iron layered double hydroxide.
[0008] The inventors have found that the catalyst based on nickel-iron layered double hydroxide can be used as an oxygen evolution reaction catalyst in an electrolyte with a high concentration of alkaline solution (e.g., a KOH aqueous solution with a concentration greater than or equal to 1 mol / L). -2 ), the surface reaction rate of nickel-iron layered double hydroxide will be accelerated, resulting in the generation of a large number of protons. In a high concentration alkaline solution, a sufficient amount of OH in the solution - Ions can act as proton acceptors to neutralize these generated protons in a short time, thus ensuring the high catalytic stability of the catalyst. - The ion concentration is low, and the protons generated on the catalyst surface cannot be neutralized in a short period of time, causing a large number of protons to accumulate on the catalyst surface in a short period of time, which in turn causes the active components of the catalyst to fall off from the substrate and / or the metal sites of the catalyst to precipitate, reducing the stability of the catalyst.
[0009] The dispersed Lewis acid compound particles formed on the surface of NiFe LDH can serve as OH - The adsorption sites of ions can effectively increase the OH - ion concentration, so that they can recombine with protons in time, thereby reducing the proton concentration on the catalyst surface, reducing the damage of protons to the catalyst, and improving the catalytic stability of the catalyst under industrial-grade current density.
[0010] However, excessive loading of Lewis acid compound particles dispersed on the surface of nickel-iron layered double hydroxide will cause the catalytic sites on the NiFe LDH catalyst to be covered, and the number of catalytic sites will become relatively small, which will affect the catalytic activity of the catalyst.
[0011] Preferably, the substrate is selected from but not limited to at least one of nickel foam, iron foam, nickel iron foam, nickel mesh, iron mesh, nickel iron mesh, nickel felt, iron felt, and nickel iron felt;
[0012] Preferably, the average particle size of the Lewis acid compound particles is 15-25 nm;
[0013] Preferably, the Lewis acid compound is selected from Lewis acid metal oxides;
[0014] Preferably, the Lewis acid compound is selected from MnO X ;
[0015] More preferably, the Lewis acid compound is trimanganese tetraoxide.
[0016] Preferably, the proportion of the metal element in the Lewis acid metal oxide to the total mass of the Lewis acid metal oxide and the nickel-iron layered double hydroxide is 0.1-0.2 wt %;
[0017] Further preferably, the weight ratio of the metal element in the Lewis acid metal oxide to the total weight of the Lewis acid metal oxide and the nickel-iron layered double hydroxide is 0.17 wt %.
[0018] The present invention provides a method for preparing the heterogeneous structure composite catalyst described above, comprising the following steps: forming a nickel-iron layered double hydroxide on the surface of a substrate to obtain a composite catalyst precursor, and then forming Lewis acid compound particles on the surface of the nickel-iron layered double hydroxide of the catalyst precursor to obtain the heterogeneous structure composite catalyst.
[0019] Preferably, the preparation of the composite catalyst precursor comprises the following steps: preparing a hydrolyzable metal salt solution, adjusting the pH of the hydrolyzable metal salt solution to 2.5-6.5 to form a first mixed solution; placing the substrate in the first mixed solution and allowing it to stand, and then adding a first organic solvent to react, thereby obtaining the composite catalyst precursor;
[0020] Optionally, the pH of the hydrolyzable metal salt solution is regulated by adding an acid;
[0021] Optionally, the acid is selected from at least one of sulfuric acid, hydrochloric acid and nitric acid;
[0022] Optionally, the process of adding the first organic solvent is performed under ultrasonic stirring conditions;
[0023] Preferably, the hydrolyzable metal salt includes at least one of nickel chloride, nickel sulfate, nickel nitrate, ferric sulfate, ferrous sulfate, ferric chloride, and ferrous chloride;
[0024] Preferably, the hydrolyzable metal salt is selected from at least one of ferrous sulfate and ferrous chloride;
[0025] Preferably, the concentration of the hydrolyzable metal salt in the hydrolyzable metal salt solution is 0.02-0.4 mol / L;
[0026] Preferably, the first organic solvent is selected from at least one of acetone, methanol, ethanol, propanol, isopropanol, allyl alcohol, butanol, 2-butanol, tert-butanol, ethylene glycol, propylene glycol, tetrahydrofuran, dimethyl ether, ethyl acetate, and N,N-dimethylformamide;
[0027] Preferably, the solvent in the hydrolyzable metal salt solution is water;
[0028] Preferably, the volume ratio of the first organic solvent to the first mixed solution is (0.5-9):1;
[0029] Preferably, the substrate is selected from at least one of nickel foam, iron foam, nickel-iron foam, nickel mesh, iron mesh, nickel-iron mesh, nickel felt, iron felt, and nickel-iron felt;
[0030] Preferably, the substrate is selected from at least one of nickel foam, nickel-iron foam, nickel mesh, nickel-iron mesh, nickel felt, and nickel-iron felt.
[0031] The standing temperature is 5-50°C; the standing time is 0.1-5h;
[0032] Preferably, the reaction temperature is 20-40°C; and the reaction time is 10-40h.
[0033] Preferably, the process of forming manganese tetraoxide particles on the surface of nickel-iron layered double hydroxide of the catalyst precursor comprises the following steps:
[0034] Mixing a manganese salt solution and an alkali solution to form a second mixed solution, placing a composite catalyst precursor in the second mixed solution to perform a solvothermal reaction, and obtaining the heterogeneous structure composite catalyst;
[0035] Preferably, the molar ratio of the manganese salt to the base in the second mixed solution is (0.8-1.2):(0.1-0.35);
[0036] Preferably, the manganese salt concentration in the manganese salt solution is 0.003-0.005 mol / L;
[0037] Preferably, the alkali concentration in the alkali solution is 0.008-0.012 mol / L;
[0038] Preferably, the solvent of the manganese salt solution is a mixture of water and a second organic solvent; wherein the volume ratio of water to the second organic solvent is (0.8-1.2): (20-28);
[0039] Preferably, the manganese salt is selected from but not limited to manganese acetate, manganese nitrate, and manganese chloride;
[0040] Preferably, the second organic solvent is selected from but not limited to at least one of acetone, methanol, ethanol, propanol, isopropanol, allyl alcohol, butanol, 2-butanol, tert-butanol, ethylene glycol, propylene glycol, tetrahydrofuran, dimethyl ether, ethyl acetate, and N,N-dimethylformamide;
[0041] Preferably, the alkali in the alkali solution is selected from but not limited to at least one of NaOH and KOH.
[0042] Preferably, the solvent thermal reaction temperature is 150-190° C., and the reaction time is 1-3 h.
[0043] Optionally, the process of mixing the manganese salt solution and the alkali solution to form the second mixed solution is to drop the alkali solution into the manganese salt solution during stirring.
[0044] Optionally, the process of placing the composite catalyst precursor in the second mixed solution for solvothermal reaction further includes a washing and drying process;
[0045] Optionally, the cleaning process is cleaning with ionized water and ethanol;
[0046] Optionally, the drying process is room temperature drying under vacuum conditions.
[0047] The present invention also provides an application of the heterogeneous structure composite catalyst described above or the heterogeneous structure composite catalyst prepared above in hydrogen production by electrolysis of water.
[0048] Preferably, the electrolysis of water to produce hydrogen is anion exchange membrane electrolysis of water to produce hydrogen; the electrolyte for the electrolysis of water to produce hydrogen is alkaline solution;
[0049] Preferably, the alkali in the alkali solution is KOH;
[0050] Preferably, the base concentration is less than or equal to 1 mol / L;
[0051] Preferably, the base concentration is less than or equal to 0.5 mol / L;
[0052] Preferably, the alkali concentration is less than or equal to 0.1 mol / L.
[0053] Preferably, the heterogeneous structure composite catalyst described above or the heterogeneous structure composite catalyst prepared above is used as a working electrode; Hg / HgO is used as a reference electrode, and a platinum mesh is used as a counter electrode.
[0054] The present invention also provides an anion exchange membrane electrolyzer, comprising a membrane electrode, wherein the membrane electrode comprises an anion exchange membrane, and one side of the anion exchange membrane comprises the heterogeneous structure composite catalyst prepared as described above.
[0055] Optionally, the anion exchange membrane electrolyzer further comprises a reference electrode and a counter electrode;
[0056] Optionally, the reference electrode is Hg / HgO; and the counter electrode is a platinum mesh.
[0057] The technical solution of the present invention has the following advantages:
[0058] The heterogeneous structure composite catalyst provided by the invention comprises: a substrate, nickel-iron layered double hydroxide located on the surface of the substrate and Lewis acid compound particles dispersed on the surface of the nickel-iron layered double hydroxide.
[0059] The heterogeneous structure composite catalyst provided by the present invention uses low-concentration alkali as the electrolyte. Under the condition of industrial-grade current density, the nickel-iron layered double hydroxide can quickly precipitate oxygen as an excellent oxygen evolution reaction catalyst and generate a large number of protons on the surface; the Lewis acid compound particles dispersed on the surface of the nickel-iron layered double hydroxide act as OH - The adsorption sites of ions can effectively increase the OH - ion concentration, so that it can recombine with protons in time, thereby reducing the proton concentration on the catalyst surface, reducing the damage of protons to the catalyst, and improving the catalytic stability of the catalyst at industrial-grade current density;
[0060] Furthermore, the Lewis acid compound particles dispersed on the surface of the nickel-iron layered double hydroxide and the nickel-iron layered double hydroxide work synergistically to significantly improve the activity of the catalyst, thereby increasing the rate of the oxygen evolution reaction;
[0061] Furthermore, the heterogeneous structure composite catalyst provided in the present application is suitable for the electrolysis of water to produce hydrogen in a low concentration alkali solution environment, and does not require the use of an additional anion ionomer as OH - The anion exchange membrane electrolyzer can bridge the ions, thereby avoiding the problem of weak adhesion and chemical stability of the anion ionomer itself, which causes the energy conversion efficiency of the anion exchange membrane electrolyzer to decrease during long-term operation, thereby improving the operating stability of the anion exchange membrane electrolyzer.
[0062] Furthermore, the preparation method provided by the present invention is simple and easy to scale up, and has important research significance for realizing the industrial application of AEM electrolysis of water in low-concentration alkaline solution system. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0064] Figure 1 is a scanning electron microscope image of the heterostructured Mn3O4 / NiFe LDH-NF electrode in Example 1 of the present invention;
[0065] Figure 2 is a local magnified scanning electron microscope image of the heterostructured Mn3O4 / NiFe LDH-NF electrode in Example 1 of the present invention;
[0066] Figure 3 is a transmission electron microscope image of the heterostructured Mn3O4 / NiFe LDH-NF electrode in Example 1;
[0067] Figure 4 is a local magnified transmission electron microscopy image of the heterostructured Mn3O4 / NiFe LDH-NF electrode in Example 1;
[0068] Figure 5 is the X-ray diffraction pattern of the Mn3O4 / NiFe LDH powder in Example 1;
[0069] Figure 6 LSV curves of OER in 0.1M KOH solution of the heterostructured Mn3O4 / NiFe LDH-NF electrode obtained in Example 1, the NF electrode obtained in Comparative Example 1, the electrode obtained in Comparative Example 2, and the electrode obtained in Comparative Example 3;
[0070] Figure 7 The EIS curves of the heterostructured Mn3O4 / NiFe LDH-NF electrode obtained in Example 1, the electrode obtained in Comparative Example 2, and the electrode obtained in Comparative Example 3 in 0.1M KOH solution are shown in FIG.
[0071] Figure 8 The heterostructured Mn3O4 / NiFe LDH-NF electrode obtained in Example 1 and the electrode obtained in Comparative Example 2 were subjected to 0.5A cm -2 Vt curves at constant current density. DETAILED DESCRIPTION
[0072] The following examples are provided to further understand the present invention better, are not limited to the best mode, and are not intended to limit the content and scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the enlightenment of the present invention or by combining the features of the present invention with other prior arts, all falls within the protection scope of the present invention. If no specific experimental steps or conditions are indicated in the examples, the operation or conditions of the conventional experimental steps described in the literature in this area can be carried out. If the manufacturer is not indicated for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0073] The nickel foam used in the examples and comparative examples of the present invention was purchased from Suzhou Christie's Company, with a ppi of 80.
[0074] Example 1
[0075] This embodiment provides a method for preparing a heterogeneous structure composite catalyst electrode, which specifically includes the following steps:
[0076] (1) dissolving a certain amount of easily hydrolyzed ferrous chloride metal salt in water, stirring to form a solution with a metal ion concentration of 100 mmol / L, adjusting the pH to 3.5 with sulfuric acid to obtain a first mixed solution; 2 The nickel foam is placed in a first mixed solution and allowed to stand at 30° C. for 4 hours. Under ultrasonic stirring conditions, ethanol is slowly added to the first mixed solution system containing the nickel foam (the volume ratio of ethanol to the first mixed solution is 3:1) to form a heterogeneous liquid phase system. The system is allowed to stand at 40° C. for 24 hours. After being taken out, it is rinsed with water and dried to obtain NiFe LDH-NF (a composite catalyst precursor, the composite catalyst precursor comprising a nickel foam substrate and a nickel-iron layered double hydroxide located on the surface of the nickel foam substrate);
[0077] (2) 0.1 mmol of manganese acetate was weighed and dissolved in a mixed solution of 1.0 mL of deionized water and 24.0 mL of ethanol to obtain a manganese acetate solution. During continuous stirring, 2.5 mL of 10 mmol / L KOH was dropwise added to the manganese acetate solution. After the dropwise addition was completed, stirring was stopped to obtain a second mixed solution. The second mixed solution was transferred to a 50 mL polytetrafluoroethylene reactor, and the NiFe LDH-NF prepared in step (1) was added, and reacted at 175° C. for 1 h. After natural cooling, the reaction was taken out, and the mixture was repeatedly washed with deionized water and ethanol, and then naturally dried under vacuum conditions to obtain a heterostructured Mn3O4 / NiFe LDH-NF electrode (i.e., the heterostructured composite catalyst electrode), wherein the average particle size of the manganese tetraoxide particles was 20 nm, and the proportion of manganese element in the manganese tetraoxide to the total mass of the manganese tetraoxide and the nickel-iron layered double hydroxide was 0.17 wt%.
[0078] Example 2
[0079] This embodiment provides a method for preparing a heterogeneous structure composite catalyst electrode, which specifically includes the following steps:
[0080] (1) Dissolve a certain amount of easily hydrolyzed ferrous chloride metal salt in water, stir to form a solution with a metal ion concentration of 200 mmol / L, adjust the pH to 3.5 with sulfuric acid to obtain a first mixed solution; 2 The nickel foam is placed in the first mixed solution and allowed to stand at 30° C. for 4 hours. Under ultrasonic stirring conditions, ethanol is slowly added to the first mixed solution system containing the nickel foam (the volume ratio of ethanol to the first mixed solution is 3:1) to form a heterogeneous liquid phase system. The system is allowed to stand at 25° C. for 36 hours. After being taken out, it is rinsed with water and dried to obtain NiFe LDH-NF (composite catalyst precursor).
[0081] (2) Weigh 0.1 mmol of manganese nitrate and dissolve it in a mixed solution of 1.0 mL of deionized water and 24.0 mL of ethanol to obtain a manganese acetate solution. While stirring continuously, add 3 mL of 10 mmol / L NaOH dropwise into the manganese nitrate solution. After the addition is complete, stop stirring to obtain a second mixed solution. Transfer the second mixed solution to a 50 mL polytetrafluoroethylene reactor, add the NiFe LDH-NF prepared in step (1), react at 180° C. for 2 h, take out after natural cooling, repeatedly wash with deionized water and ethanol, and then dry naturally under vacuum conditions to obtain a heterostructured Mn3O4 / NiFe LDH-NF electrode (i.e., the heterostructured composite catalyst electrode).
[0082] Example 3
[0083] This embodiment provides a method for preparing a heterogeneous structure composite catalyst electrode, which specifically includes the following steps:
[0084] (1) Dissolve a certain amount of easily hydrolyzed ferrous chloride metal salt in water, stir to form a solution with a metal ion concentration of 200 mmol / L, adjust the pH to 6.5 with sulfuric acid to obtain a first mixed solution; 2 The nickel foam is placed in the first mixed solution and allowed to stand at 5°C for 5 hours. Under ultrasonic stirring conditions, ethanol is slowly added to the first mixed solution system containing the nickel foam (the volume ratio of ethanol to the first mixed solution is 0.5:1) to form a heterogeneous liquid phase system. The system is allowed to stand at 20°C for 40 hours. After being taken out, it is rinsed with water and dried to obtain NiFe LDH-NF (composite catalyst precursor).
[0085] (2) Weigh 0.1 mmol of manganese chloride and dissolve it in a mixed solution of 1.0 mL of deionized water and 24.0 mL of isopropanol to obtain a manganese chloride solution. While stirring continuously, add 2 mL of 10 mmol / L KOH dropwise to the manganese chloride solution. After the addition is complete, stop stirring to obtain a second mixed solution. Transfer the second mixed solution to a 50 mL polytetrafluoroethylene reactor, add the NiFe LDH-NF prepared in step (1), react at 160° C. for 3 h, take out after natural cooling, repeatedly wash with deionized water and ethanol, and then dry naturally under vacuum conditions to obtain a heterostructured Mn3O4 / NiFe LDH-NF electrode (i.e., the heterostructured composite catalyst electrode).
[0086] Comparative Example 1
[0087] This comparative example provides a method for preparing a nickel foam (NF) electrode, comprising the following steps: ultrasonically cleaning a nickel foam (NF) having a size of 1.5*3.0 cm2 in 1M hydrochloric acid for 30 min, and then drying to obtain a nickel foam (NF) electrode.
[0088] Comparative Example 2
[0089] The present comparative example provides a method for preparing an electrode, comprising the following steps: dissolving a certain amount of easily hydrolyzed ferrous chloride metal salt in water, stirring to form a solution with a metal ion concentration of 100 mmol / L, adjusting the pH to 3.5 with sulfuric acid to obtain a first mixed solution; 2 The nickel foam is placed in the first mixed solution and allowed to stand at 30°C for 4 hours. Under ultrasonic stirring, ethanol is slowly added to the first mixed solution system containing the nickel foam (the volume ratio of ethanol to the first mixed solution is 3:1) to form a heterogeneous liquid phase system. The system is allowed to stand at 40°C for 24 hours. After being taken out, it is rinsed with water and dried to obtain an electrode.
[0090] Comparative Example 3
[0091] The present comparative example provides a method for preparing an electrode, comprising the following steps: ultrasonically cleaning an initial nickel foam (NF) having a size of 1.5*3.0 cm2 in 1M hydrochloric acid for 30 min, and then drying it; weighing 0.1 mmol of manganese acetate and dissolving it in a mixed solution of 1.0 mL of deionized water and 24.0 mL of ethanol to obtain a manganese acetate solution, and in a process of continuous stirring, adding 2.5 mL of 10 mmol / L KOH dropwise to the manganese acetate solution, and after the dropwise addition is completed, stopping stirring to obtain a second mixed solution; transferring the second mixed solution to a 50 mL polytetrafluoroethylene reactor, adding the dried NF, reacting at 175°C for 1 h, taking it out after natural cooling, repeatedly washing it with deionized water and ethanol, and then naturally drying it under vacuum conditions to obtain the electrode.
[0092] Test Case
[0093] 1. Scanning electron microscopy, transmission electron microscopy, X-ray analysis
[0094] The prepared electrodes were analyzed using scanning electron microscopy, transmission electron microscopy and X-ray instrument.
[0095] Figure 1 is a scanning electron microscope image of the heterostructured Mn3O4 / NiFe LDH-NF electrode in Example 1, Figure 2 This is a local magnified scanning electron microscope image of the heterostructured Mn3O4 / NiFe LDH-NF electrode in Example 1. It can be seen from the figure that the in-situ grown NiFe LDH nanosheets (nickel-iron layered double hydroxide) are uniformly and densely loaded on the NF skeleton. After the solvothermal reaction in step (2), it can be clearly found that the Mn3O4 nanoparticles are uniformly loaded on the NiFe LDH nanosheets, indicating the successful preparation of the heterostructured Mn3O4 / NiFe LDH-NF electrode.
[0096] Figure 3 is a transmission electron microscope image of the heterostructured Mn3O4 / NiFe LDH-NF electrode in Example 1, Figure 4 This is a partial magnified transmission electron micrograph of the heterostructured Mn3O4 / NiFe LDH-NF electrode in Example 1. Figure 3 , Figure 4 It can be seen that the Mn3O4 nanoparticles are uniformly loaded on the NiFe LDH nanosheets, which is consistent with the results of SEM analysis. In addition, high-resolution TEM analysis found that the plane with a crystal plane spacing of 0.16nm is the (112) plane of Mn3O4, and the plane with a crystal plane spacing of 0.15nm is the (110) plane of NiFe LDH, which once again proves the formation of Mn3O4 / NiFe LDH heterostructure.
[0097] Figure 5 It is the X-ray diffraction pattern of the Mn3O4 / NiFe LDH powder in Example 1. In order to eliminate the signal interference of the NF substrate, the NF substrate was peeled off by ultrasound before the X-ray test, and the structure of the synthesized catalyst was analyzed by testing the collected powder. It can be seen from the figure that in addition to the typical characteristic peaks of NiFe LDH, the peaks with diffraction angles of 17.7° and 36.2° can be attributed to the (112) and (211) planes of Mn3O4, respectively, which also proves the successful synthesis of the Mn3O4 / NiFe LDH heterostructure.
[0098] 2. Electrochemical testing
[0099] The electrochemical test uses a 0.1 mol / L KOH solution as the electrolyte. At room temperature, the electrode prepared in the embodiment and the comparative example is the working electrode, Hg / HgO is used as the reference electrode, and the platinum mesh is used as the counter electrode. The electrochemical test is performed using an autolab electrochemical workstation. Before the electrochemical test, the working electrode is first subjected to a scanning activation of the cyclic voltammetry curve (CV), and the scanning voltage range is 0.2 to 1.0 V (vs. Hg / HgO), and the scanning speed is 100.0 mV / s. After the CV curve remains stable, a linear voltammetry scan (LSV) test is performed. The voltage range of the LSV test is 0.2 to 1.0 V (vs. Hg / HgO), and the scanning speed is 5.0 mV / s. The LSV curve is compensated by manual iR correction. Figure 6 : The LSV curves of the heterostructured Mn3O4 / NiFe LDH-NF electrode obtained in Example 1, the NF electrode obtained in Comparative Example 1, the electrode obtained in Comparative Example 2, and the electrode obtained in Comparative Example 3 in 0.1M KOH solution. It can be seen from the figure that the electrode in Example 1 exhibits the highest electrocatalytic OER activity, reaching 0.5A cm -2 The overpotential required for the current density is only 300 mV, indicating that the coupling of Mn3O4 and NiFe LDH effectively promotes the enhancement of OER catalytic activity.
[0100] Subsequently, the alternating current impedance (EIS) of the electrodes prepared in the examples and comparative examples was tested at a voltage of 0.6 V (vs. Hg / HgO), and the test frequency range of the impedance was 100 KHz-0.1 Hz, and the amplitude was 10 mV. Figure 7 The EIS curves of the heterostructured Mn3O4 / NiFe LDH-NF electrode obtained in Example 1, the electrode obtained in Comparative Example 2, and the electrode obtained in Comparative Example 3 in 0.1M KOH solution. Due to the weak OER response of the NF substrate, the electrochemical impedance test of NF is excluded here. As can be seen from the figure, the semicircle diameter of the EIS curve represented by the heterostructured Mn3O4 / NiFe LDH-NF electrode obtained in Example 1 is the smallest, indicating that the introduction of Mn3O4 accelerates the charge transfer during the catalyst reaction, improves the kinetics of the OER reaction, and promotes the improvement of the OER catalytic activity.
[0101] The stability of the working electrode was tested by the constant current (CP) method with a current density of 0.5 A cm -2 . Figure 8 The heterostructured Mn3O4 / NiFe LDH-NF electrode obtained in Example 1 and the electrode obtained in Comparative Example 2 were subjected to 0.5A cm -2Vt curve under constant current density. It can be seen from the figure that after 80 hours of electrolysis, for the electrode obtained in Comparative Example 2, the current density of 0.5A cm -2 The voltage required for the constant current density increased significantly (increase rate 1.25 mV / h). For the heterostructured Mn3O4 / NiFe LDH-NF electrode obtained in Example 1, after 800 h of electrolysis, it maintained 0.5 A cm -2 The voltage required for constant current density did not change significantly, which showed that Mn3O4 could adsorb more OH on the catalyst surface after Lewis coupling with NiFe LDH. - , increasing the OH on the catalyst surface during electrolysis - The ion concentration is increased, which effectively alleviates the enrichment of protons on the NiFe LDH surface during high current density electrolysis and improves the OER stability of the catalyst. The stable operation time of the electrodes prepared in the examples and comparative examples is shown in Table 1.
[0102] Table 1
[0103] Stable running time (h) Example 1 800 Example 2 700 Example 3 750 Comparative Example 1 10 Comparative Example 2 100 Comparative Example 3 15
[0104] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A heterogeneous structure composite catalyst, characterized in that: include: A substrate, a nickel-iron layered double hydroxide located on the surface of the substrate, and Lewis acid compound particles dispersed on the surface of the nickel-iron layered double hydroxide.
2. The composite catalyst according to claim 1, characterized in that The substrate is selected from at least one of foamed nickel, foamed iron, foamed nickel-iron, nickel mesh, iron mesh, nickel-iron mesh, nickel felt, iron felt, and nickel-iron felt; Preferably, the average particle size of the Lewis acid compound particles is 15-25 nm; Preferably, the Lewis acid compound is selected from Lewis acid metal oxides; Preferably, the Lewis acid compound is selected from MnO X ; Further preferably, the Lewis acid compound is manganese tetraoxide; Preferably, the proportion of the metal element in the Lewis acid metal oxide to the total mass of the Lewis acid metal oxide and the nickel-iron layered double hydroxide is 0.1-0.2 wt %; Further preferably, the weight ratio of the metal element in the Lewis acid metal oxide to the total weight of the Lewis acid metal oxide and the nickel-iron layered double hydroxide is 0.17 wt %.
3. A method for preparing a heterogeneous structure composite catalyst according to claim 1 or 2, characterized in that: The method comprises the following steps: forming nickel-iron layered double hydroxide on the surface of a substrate to obtain a composite catalyst precursor, and then forming Lewis acid compound particles on the surface of the nickel-iron layered double hydroxide of the catalyst precursor to obtain the heterogeneous structure composite catalyst.
4. The preparation method according to claim 3, characterized in that: The preparation of the composite catalyst precursor comprises the following steps: preparing a hydrolyzable metal salt solution, adjusting the pH of the hydrolyzable metal salt solution to 2.5-6.5 to form a first mixed solution; placing a substrate in the first mixed solution and letting it stand, then adding a first organic solvent to react, thereby obtaining the composite catalyst precursor; Preferably, the hydrolyzable metal salt includes at least one of nickel chloride, nickel sulfate, nickel nitrate, ferric sulfate, ferrous sulfate, ferric chloride, and ferrous chloride; Preferably, the hydrolyzable metal salt is selected from at least one of ferrous sulfate and ferrous chloride; Preferably, the concentration of the hydrolyzable metal salt in the hydrolyzable metal salt solution is 0.02-0.4 mol / L; Preferably, the first organic solvent is selected from at least one of acetone, methanol, ethanol, propanol, isopropanol, allyl alcohol, butanol, 2-butanol, tert-butanol, ethylene glycol, propylene glycol, tetrahydrofuran, dimethyl ether, ethyl acetate, and N,N-dimethylformamide; Preferably, the solvent in the hydrolyzable metal salt solution is water; Preferably, the volume ratio of the first organic solvent to the first mixed solution is (0.5-9):1; Preferably, the substrate is selected from at least one of nickel foam, iron foam, nickel-iron foam, nickel mesh, iron mesh, nickel-iron mesh, nickel felt, iron felt, and nickel-iron felt; Preferably, the substrate is selected from at least one of nickel foam, nickel-iron foam, nickel mesh, nickel-iron mesh, nickel felt, and nickel-iron felt.
5. The preparation method according to claim 4, characterized in that: The standing temperature is 5-50°C; the standing time is 0.1-5h; Preferably, the reaction temperature is 20-40°C; and the reaction time is 10-40h.
6. The preparation method according to claim 3, characterized in that: The process of forming Lewis acid compound particles on the surface of nickel-iron layered double hydroxide of the catalyst precursor comprises the following steps: Mixing a manganese salt solution and an alkali solution to form a second mixed solution, placing a composite catalyst precursor in the second mixed solution to perform a solvothermal reaction, and obtaining the heterogeneous structure composite catalyst; Preferably, the molar ratio of the manganese salt to the base in the second mixed solution is (0.8-1.2):(0.1-0.35); Preferably, the manganese salt concentration in the manganese salt solution is 0.003-0.005 mol / L; Preferably, the alkali concentration in the alkali solution is 0.008-0.012 mol / L; Preferably, the solvent of the manganese salt solution is a mixture of water and a second organic solvent; wherein the volume ratio of water to the second organic solvent is (0.8-1.2): (20-28); Preferably, the second organic solvent is selected from at least one of acetone, methanol, ethanol, propanol, isopropanol, allyl alcohol, butanol, 2-butanol, tert-butanol, ethylene glycol, propylene glycol, tetrahydrofuran, dimethyl ether, ethyl acetate, and N,N-dimethylformamide; Preferably, the manganese salt is selected from manganese acetate, manganese nitrate, and manganese chloride; Preferably, the alkali in the alkali solution is selected from at least one of NaOH and KOH.
7. The preparation method according to claim 6, characterized in that: The solvent thermal reaction temperature is 150-190°C and the reaction time is 1-3h.
8. Use of the heterogeneous structure composite catalyst according to claim 1 or 2 or the prepared heterogeneous structure composite catalyst according to any one of claims 1 to 7 in hydrogen production by electrolysis of water.
9. The use according to claim 8, characterized in that: The electrolysis of water to produce hydrogen is carried out by electrolysis of water using an anion exchange membrane; the electrolyte used in the electrolysis of water to produce hydrogen is alkaline solution; Preferably, the alkali in the alkali solution is KOH; Preferably, the base concentration is less than or equal to 1 mol / L; Preferably, the base concentration is less than or equal to 0.5 mol / L; Preferably, the alkali concentration is less than or equal to 0.1 mol / L.
10. An anion exchange membrane electrolyzer, characterized in that: It comprises a membrane electrode, wherein the membrane electrode comprises an anion exchange membrane, and one side of the anion exchange membrane comprises the heterogeneous structure composite catalyst according to claim 1 or 2 or the prepared heterogeneous structure composite catalyst according to any one of claims 1-7.
Citation Information
Cited By
High-entropy oxide composite nickel-iron layered double hydroxide catalyst as well as preparation method and application thereof
CN121451230A
Oxygen evolution reaction catalyst, preparation method therefor, and use thereof
WO2025162048A1
